Informal Institutions and the Complexity of Joint Action in Indonesian Governance - Ricky Putra (POPULIKA, 2026)
Governance requires diverse institutions with varying backgrounds to act in concert as representatives of the state. However, in the Indonesian context, joint actions reach a high degree complexity due to deeply seated and overpowering informal institutions. These informal institutions can dictate bureaucratic behavior and shape public perception of the state’s overall governance. This study explores the connection between the influence of informal institutions and the complexity of joint actions. Utilizing data from secondary sources-including open-access journals and official online database-the study examines the relationships between sudden policy implementation by central authorities, the subsequent vacuum of authority, informal institutions, weak oversight, and the implementation of repressive policies by populist leaders. Ultimately, this research finds that the joint actions necessary for governance in Indonesia are heavily influenced by informality. These informal structures emerge when the rapid implementation of policies is not paired with the necessary technical knowledge. The resulting effect is poor bureaucratic performance, where corrective efforts, such as institutional oversight, are hindered by the same informality affecting other formal institutions. Consequently, this study concludes that sudden reforms are counterproductive and instead advocates for the gradual development of the technical expertise required to execute modern governance.